2021
DOI: 10.1097/iae.0000000000002970
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dilated Subfoveal Choroidal Veins in Eyes With Myopic Macular Neovascularization

Abstract: To investigate the dilated choroidal veins (DCVs) at or around myopic macular neovascularizations (MNVs) and to determine whether there is a hemodynamic relationship between them.Methods: Fifty-eight eyes of 57 patients with myopic MNVs were examined. Dilated choroidal veins were defined as choroidal veins whose diameter was 2X larger than adjacent veins. Indocyanine green angiography and swept-source optical coherence tomography images were reviewed to detect DCVs that crossed the subfoveal area. The filling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…To date, this feature has been exclusively reported in this condition. In two studies, Xie et al reported that a dilated choroidal vein was correlated with the occurrence 20 and the recurrence 19 of MNVs. Moriyama et al 18 also showed a HM eye that developed MNV just over a dilated choroidal vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, this feature has been exclusively reported in this condition. In two studies, Xie et al reported that a dilated choroidal vein was correlated with the occurrence 20 and the recurrence 19 of MNVs. Moriyama et al 18 also showed a HM eye that developed MNV just over a dilated choroidal vein.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition to the extreme thinning, the remaining large choroidal veins were reported to have marked changes in PM eyes. 18–20 These studies used mainly the 50° ICGA indocyanine green angiography (ICGA) images, and to date, there are limited data on how the choroidal vasculature is altered over the entire fundus in a large population of PM eyes. Therefore, in the present study, we used widefield ICGA (WF-ICGA) to explore choroidal venous remodeling patterns in the entire fundus, so as to unravel the mechanisms of remodeling and their clinical implications.…”
mentioning
confidence: 99%
“…More recently, the same group reported the presence of dilated subfoveal choroidal veins (DCVs) below or around the neovascular complex in 30% of the eyes with mCNV. 30 The authors suggested that mCNV receive the flow from the SPCA and drain to the dilated subfoveal choroidal veins. They stated that SPCAs are filled first, followed by mCNV, which then drain to the dilated subfoveal choroidal veins, and talked about the possible role that chronic choroidal venous congestion may play on the development of mCNV in eyes with PM.…”
Section: Discussionmentioning
confidence: 99%
“…However, shadows do not always appear. For instance, Xie et al 30 recently reported that a dilated choroidal vein beneath CNV was observed in 30% of mCNV eyes. One mechanism underlying the CFD around CNV might be choriocapillaris exclusion by the choroidal vein.…”
Section: Discussionmentioning
confidence: 99%